Neurofeedback: Principles, appraisal, and outstanding issues. (13th February 2019) - Papo, David
Abstract: Neurofeedback is a form of brain training in which subjects are fed back information about some measure of their brain activity which they are instructed to modify in a way thought to be functionally advantageous. Over the last 20 years, neurofeedback has been used to treat various neurological and psychiatric conditions, and to improve cognitive function in various contexts. However, in spite of a growing popularity, neurofeedback protocols typically make (often covert) assumptions on what aspects of brain activity to target, where in the brain to act and how, which have far‐reaching implications for the assessment of its potential and efficacy. Here we critically examine some conceptual and methodological issues associated with the way neurofeedback's general objectives and neural targets are defined. The neural mechanisms through which neurofeedback may act at various spatial and temporal scales, and the way its efficacy is appraised are reviewed, and the extent to which neurofeedback may be used to control functional brain activity discussed. Finally, it is proposed that gauging neurofeedback's potential, as well as assessing and improving its efficacy will require better understanding of various fundamental aspects of brain dynamics and a more precise definition of functional brain activity and brain‐behaviour relationships. Abstract : Neurofeedback protocols typically make restrictive assumptions on what aspects of brain activity to target, where in the brain to act and how, which have far‐reaching implications for the assessment of neurofeedback's potential and efficacy. Here, we critically examine some conceptual and methodological issues associated with the way neurofeedback's general objectives and neural targets are defined, and discuss the neural mechanisms through which it may act, the way its efficacy is appraised, and the extent to which it may be used to control brain function.